2021
DOI: 10.21037/jgo-21-720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PPP2CA expression on the prognosis of patients with hepatocellular carcinoma and its molecular biological characteristics

Abstract: Background: To investigate the role of the PPP2CA gene in the prognosis of patients with hepatocellular carcinoma (HCC) and its molecular biological characteristics. Methods: We performed comparison of the expression of PPP2CA in HCC and non-HCC tissues of HCC patients who underwent surgery for the first time in the Tumor Hospital of Guangxi Medical University from July 2017 to July 2019, and retrospectively analyzed the relevant clinical data and prognosis. The GSE76427 data set and bioinformatics and public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[ 23 ] found that DEAD-box helicase 3, X-linked (DDX3X) is associated with liver injury and liver tumour development through chromosome segregation. Regarding organelle fission, high expression of the PPP2CA gene in HCC tissue is significantly associated with poor prognosis of liver cancer patients, and the PPP2CA gene and related genes in the study are also enriched in organelle fission [ 24 ]. KEGG enrichment analysis showed that the main pathways of differential genes are cell cycle, retinol metabolism, metabolism of xenobiotics by cytochrome P450, and drug metabolism−cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] found that DEAD-box helicase 3, X-linked (DDX3X) is associated with liver injury and liver tumour development through chromosome segregation. Regarding organelle fission, high expression of the PPP2CA gene in HCC tissue is significantly associated with poor prognosis of liver cancer patients, and the PPP2CA gene and related genes in the study are also enriched in organelle fission [ 24 ]. KEGG enrichment analysis showed that the main pathways of differential genes are cell cycle, retinol metabolism, metabolism of xenobiotics by cytochrome P450, and drug metabolism−cytochrome P450.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that RGS20 promotes the development of cancer by regulating the PI3K/AKT signal pathway in cancer cells [39] . The expression level of SAC3D1 [ 40 , 41 ], PPP2CA [ 42 , 43 ], PTTG1IP [44] genes is significantly increased in tumor cells and can be used as a cancer marker.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical carcinogenesis of abnormal metabolic pathways has been linked to alcoholic liver disease, depression, and several cancers, including stomach cancer [111,112]. Significant differences in the metabolism of xenobiotics by the cytochrome P450 metabolic pathway were also observed in liver cancer, gastric cancer, and alcoholic liver injury [112,113]. These results suggest the potential regulatory functions of these metabolic pathways in the therapeutic mechanism of NCVP on Pb-induced hepatorenal toxicity in mice.…”
Section: Effects Of Ncvp On Pd-induced Gut Mycobiotamentioning
confidence: 94%